Identifying the Used of Filers in Speaking Fluency of Asian Novice Teachers - Febriana Aminatul Khusna; Lilia Indriani (International Journal of English Learning and Applied Linguistics (IJELAL), 2022)
Speaking skill is a skill that must be possessed by everyone, especially for a teacher. However, for a novice teacher who is teaching, speaking fluently in front of the class for the first time it is certainly not easy. Then, not infrequently in conveying material, they often use fillers. The purpose of this descriptive qualitative research is to investigate the used of fillers in speaking fluency, especially for novice teachers in Asia. Class observation is chosen in this study to find out the concrete data. Researchers use Brown and Abeywickrama's (2010) theory as to classification of the level of fluency in speaking. This research was conducted at one of the state universities in Indonesia. As a result, the level of fluency which was followed by 16 novice teachers in Asia was classified as good with a presentation of 48.6%. In addition, the researcher also found that the use of filers showed the number 1,215 consisting of 12 fillers words. However, this percentage of numbers shows that the novice teachers are strongly advised to reduce the use of these fillers.